2022
DOI: 10.3390/su14084432
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization of Recycled Sewage Sludge Ash as a Supplementary Cementitious Material in Mortar: A Review

Abstract: The output of sewage sludge has been increasing in recent years in China. Traditional treatment methods, such as incineration and landfilling, cannot meet the requirement of sustainability in various industries. As one of the efficient recycling methods for sewage sludge, previous studies have proven that sewage sludge ash (SSA) can be used as a supplementary cementitious material to partly replace cement in mortar or concrete. To understand the performance of SSA comprehensively, which contributes to its bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 121 publications
2
6
0
Order By: Relevance
“…Furthermore, according to the research conducted by Donatello et al [31] compressive strength of mortar increases as the particle size of the added sludge decreases. Also, the chemical reaction between cement and silica sand could be improved due to the high fineness of sludge particles, thus resulting in a noticeable improvement in strength [32,33]. This explanation agrees with Pan et al [34], who concluded that the compressive strength of mortar made with fine sludge particles is greater than that of mortar made with coarse particles, where the fine particles provide sites for cement hydration reaction and the grinding process can enhance the pozzolanic activity of sludge.…”
Section: Compressive and Flexural Strengthssupporting
confidence: 84%
“…Furthermore, according to the research conducted by Donatello et al [31] compressive strength of mortar increases as the particle size of the added sludge decreases. Also, the chemical reaction between cement and silica sand could be improved due to the high fineness of sludge particles, thus resulting in a noticeable improvement in strength [32,33]. This explanation agrees with Pan et al [34], who concluded that the compressive strength of mortar made with fine sludge particles is greater than that of mortar made with coarse particles, where the fine particles provide sites for cement hydration reaction and the grinding process can enhance the pozzolanic activity of sludge.…”
Section: Compressive and Flexural Strengthssupporting
confidence: 84%
“…For instance, the utilization of plastic waste as a binder in construction materials or using organic waste to produce biodiesel for construction machinery exemplifies innovative approaches that align with circular economy principles. These findings resonate with studies that highlight the potential of waste materials to enhance the properties of construction materials (Lamba et al, 2021;Liang et al, 2022).…”
Section: Baltic Journal Of Real Estate Economics and Construction Man...supporting
confidence: 84%
“…Prior research suggested that WWTS addition leads to an increase in water demand influencing the consistency of the fresh mix [ 30 , 31 ], whereas the SWWTS addition decreases mechanical properties of ordinary concrete [ 27 ]. For every 5% increase on average in WWTS ash content in mortars, the fluidity decreases by 4.07% [ 32 ]. It was also found that porosity of mortar increases by 3.73% on average, for every 20% increase of WWTS ash content in cement mortars [ 32 ].…”
Section: Supplementary Cementitious Materials In Concrete Mixturesmentioning
confidence: 99%
“…For every 5% increase on average in WWTS ash content in mortars, the fluidity decreases by 4.07% [ 32 ]. It was also found that porosity of mortar increases by 3.73% on average, for every 20% increase of WWTS ash content in cement mortars [ 32 ]. Therefore, considering previous findings, LWPCP was selected as a product where the SWWTS was incorporated in the cement matrix.…”
Section: Supplementary Cementitious Materials In Concrete Mixturesmentioning
confidence: 99%